The Impact of Water Quality on Human Nutrition: A Review of the Relationship between Water Intake and Nutrient Absorption - Abubakar, Musa Yahaya; Haladu, Mohammed; Reuben, Pambani; Mathew, Twan Sale; Adam, Ansar Bilyaminu; Shamsuddeen, Ruslan (Darul Yasin Al Sys, 2024)
Water quality is intrinsically linked to human health, and ensuring access to clean and safe water is a fundamental public health goal, Water is essential to human health as it assists with nutrient delivery and digestion. The chemical, physical, and microbiological qualities of water have a substantial impact on the gastrointestinal tract's ability to absorb nutrients. Heavy metals, insecticides, and microbial infections are examples of contaminants that can hinder digestive processes, resulting in nutrient shortages and absorption. Pure, high-grade water can improve the absorption of nutrients and the effectiveness of digestion. This review examines the connection between nutrient absorption and water quality, with a particular emphasis on the effects of water pollution on human health. According to the review, nutrient absorption is greatly impacted by water quality, particularly in groups that are more sensitive. It emphasizes how crucial it is to monitor and control water quality better in order to provide the best possible nutrition and health results. This review synthesizes current research to elucidate the mechanisms through which water quality impacts nutrient absorption and overall nutritional status. It also highlights the public health implications, particularly in areas with inadequate access to clean water, and suggests interventions to improve water quality and support optimal health outcomes. water quality has a significant impact on human nutrition by influencing nutrient absorption, overall health, and hydration. Contaminants in water can interfere with nutrient absorption and cause a range of health issues, ultimately affecting the availability of essential nutrients in the body. Therefore, addressing water quality issues is crucial for promoting optimal nutrition and improving human health. The findings underscore the importance of ensuring access to clean drinking water as a fundamental component of nutritional health and public well-being.